Effectiveness of Guidance and Counseling Services in Enhancing Children’s Self-Adjustment at a Kindergarten in Ponorogo - Zulkipli Lessy; Wiwik Mulyani; Istifadatul Ghoziyah (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
Self-adjustment is a crucial function for young children in order for them to beneficially socialize and to be accepted in each new environment. Self-adjustment during early childhood education can be assisted by guidance and counseling services in the school environment. This study examined the effectiveness of such services towards enhancing children’s self-adjustment. Two kindergartens in the Sub-district of Bungkal, Ponorogo, Indonesia, were the sites visited. The study used quantitative research with a causal-comparative design. Data collection was carried out by using checklists and documentation within simple random sampling. Product-moment correlation was used to test validity and reliability. Then the Alpha Cronbach technique for data employed t-test analysis. Results showed that mean values of self-adjustment in the two schools were different and that the kindergarten school with guidance and counseling services scored higher than the school without such services. It was also observed that guidance and counseling teachers directed children's self-adjustment appropriately in a personal manner. This included providing relevant books for parents, as well as giving intensive guidance to the children whose initial adjustment was low, so that those children could better obtain suitable development.